The Quality of Life of Patients with HIV/AIDS Undergoing Antiretroviral Therapy: A Systematic Review - Putri Irwanti Sari; RTS Netisa Martawinarti; Nurmawati S. Lataima; Vivi Meiti Berhimpong (Universitas Airlangga, 2019)
Introduction: Quality of Life (QoL) is one of the most important things for a patient with HIV/AIDS. Good QoL will improve the adherence to treatment, especially antiretroviral therapy. The purpose of this study was to explore about the quality of life of the patients with HIV/AIDS undergoing antiretroviral therapy.Methods: The data was collected through a literature review from electronic databases such as Scopus, ProQuest, Google Scholar and Springerlink journal. The keywords were